Glyphosate influence on the physiological parameters of Conyza bonariensis biotypes - L. Vargas; D.R.O. Silva; D. Agostinetto; M.B. Matallo; F.M. Santos; S.D.B. Almeida; G. Chavarria; D.F.P. Silva (Planta Daninha, 2014)
The objective of this study was to determine changes in gas exchange and inhibition of EPSPs, based on the accumulation of shikimic acid in horseweed biotypes resistant and sensitive to glyphosate. Two experiments were conducted in a factorial model. The first one evaluated horseweed biotypes (one resistant and one susceptible to glyphosate), and herbicide rates (0 and 1,080 g a.e. ha ¹) applied on the weed. In the second experiment, the horseweed biotypes (susceptible and resistant to glyphosate) were evaluated in five periods as following: 0, 3, 7, 10, and 14 days after herbicide application (DAH). The photosynthetic rate, transpiration, carboxylation efficiency, and water efficiency were determined using an infrared gas analyzer (IRGA), and shikimic acid concentration by HPLC. The application of glyphosate damaged the photosynthetic parameters of the susceptible biotype, causing complete inhibition of the photosynthetic rate, transpiration rate, carboxylation efficiency and water use efficiency, starting from the 7 DAH. On the other hand, total inhibition of the photosynthetic parameters was not observed for the resistant biotype. Shikimic acid accumulation occurred in both biotypes after glyphosate application but the susceptible biotype had the highest concentrations, indicating greater sensitivity of the enzyme EPSPs. The accumulation of shikimic acid in the resistant biotype indicates that the mechanism of resistance is not related to the total insensitivity of the enzyme EPSPs to glyphosate and/or that other resistance mechanisms may be involved.